A Short History of Nearly Everything - Bryson, Bill (UK: Black Swan, 2016)
In this book Bill Bryson explores the most intriguing and consequential questions that science seeks to answer and attempts to understand everything that has transpired from the Big Bang to the rise of civilization. To that end, he apprenticed himself to a host of the world's most profound scientific minds, living and dead. His challenge is to take subjects like geology, chemistry, paleontology, astronomy, and particle physics and see if there isn't some way to render them comprehensible to people, like himself, made bored (or scared) stiff of science by school. His interest is not simply to discover what we know but to find out how we know it. How do we know what is in the center of the earth, thousands of miles beneath the surface? How can we know the extent and the composition of the universe, or what a black hole is? How can we know where the continents were 600 million years ago? How did anyone ever figure these things out?
Includes bibliographical references and index.
Keywords: Science -- Popular works; Science; Popular works